Cerdas Literasi Keuangan: Edukasi Gemar Menabung dan Pencegahan Pinjaman Ilegal di Desa Pamulihan Kabupaten Sumedang - Kurniawan, Iwan; Fitriani, Laksmi; Rahmawati, Ati; Nurmalia, Euis; Priatna, Ramdani; Jubaedah, Edah; Kurniati, Tetty (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2025)
The low level of financial literacy among rural communities, particularly in Pamulihan Village, Sumedang Regency, has created challenges in household financial management and increased vulnerability to illegal lending practices. This community service project focused on fostering saving awareness from an early age and raising public caution against illegal loans. The program was conducted by the Community Service Team of Politeknik STIA LAN Bandung, involving early childhood students of PAUD Khairunnisa and their parents as the target group. The method applied was a participatory-educative approach through interactive lectures, group discussions, and quiz-based evaluations to measure participants’ understanding. The results indicate improved knowledge among participants regarding types of savings, saving practices, and characteristics of illegal loans. Furthermore, a collective awareness emerged to start saving regularly and to avoid illegal borrowing, along with the initiation of family saving groups by participants. These findings highlight the beginning of a social transformation toward wiser and more sustainable financial behavior.